Preparation method of bionic laminated toughened graphene-polycaprolactone composite material
The graphene oxide aerogel template was prepared through the improved Hummer's method and multi-step process. Combined with vacuum-assisted impregnation and hot pressing molding, a multi-scale bionic layered structure was constructed, which solved the mechanical strength of polycaprolactone and achieved high Strength and high toughness and maintain biocompatibility.
Patent Information
- Application Number
- CN202411359290.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to achieve its mechanical toughening without affecting the properties of polycaprolactone, especially low melting point and high brittleness limit their deep application.
The improved Hummer's method was used to prepare high-purity graphene oxide, and graphene oxide aerogel template was prepared through water alcohol dialysis, directional freezing, vacuum lyophilization and other steps. Combined with vacuum-assisted impregnation and hot pressing molding technology, multi-scale bionic layering was constructed. The structure forms a graphene-polycaprolactone composite material with directional porous and lightweight characteristics.
It significantly improves the mechanical properties of graphene-polycaprolactone composites, achieves high strength and high toughness, and maintains the biocompatibility of polycaprolactone, providing a new strategy for strengthening and toughening of organic polymer materials.
Smart Images

Figure CN119239011A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphene-polycaprolactone composite material preparation, in particular to a method for preparing a bionic stacked and toughened graphene-polycaprolactone composite material. Background Art
[0002] Polycaprolactone ((C2H 10 O) n Polycaprolactone (PCL) is an organic polymer with a melting point of only 60-63°C. It is easy to process and shape, and has excellent biocompatibility, polymer compatibility, and biodegradability. It is widely used in controlled-release drug carriers, cell and tissue culture medium racks, preservatives, packaging films, adhesives, mask filters, lithium batteries, and many other aspects. However, inherent properties such as low strength and high brittleness have greatly limited the in-depth promotion and application of polycaprolactone. How to achieve mechanical toughening without affecting the properties of polycaprolactone is a key scientific issue of common concern to the medical and material science communities. Compared with artificial materials, natural materials such as mother-of-pearl have a special laminated structure of inorganic minerals and polymers interwoven and composited, which can exhibit excellent performance that exceeds their own components by multiple orders of magnitude. Material bionics provides a new structural bionic strategy for polycaprolactone to achieve structural and functional integration by studying the composition and structure-activity relationship of natural materials. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a bionic stacked and toughened graphene-polycaprolactone composite material, which is used to solve the problem of precise construction of multi-scale bionic stacked structures and controllable adjustment of mechanical toughening of low-melting point and highly brittle organic polymer materials. It can greatly improve the mechanical properties of the above-mentioned polymer materials and provide a new strategy for achieving the toughening preparation of organic polymers.
[0004] In order to achieve the above purpose, the technical solutions provided are as follows:
[0005] A method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material, characterized by comprising the following steps:
[0006] Step 1: Raw material preparation and processing: high-purity large-diameter graphene oxide was prepared by using the improved Hummer's method, and the concentration of the graphene oxide precursor solution was 2-10 mg / ml; polycaprolactone was purchased from Jinan Daigang Biotechnology Co., Ltd.;
[0007] Step 2: Preparation of graphene oxide aerogel template: Graphene oxide precursor solution is assisted by chemical crosslinking agent to obtain graphene oxide hydrogel by hydrothermal assembly, and then a graphene oxide aerogel template with directional porosity and light weight is obtained by steps of water-alcohol dialysis, directional freezing, vacuum freeze drying, etc.;
[0008] Step 3, preparation of polycaprolactone precursor solution: determine the concentration and volume of the polycaprolactone precursor solution, quantitatively weigh polycaprolactone, select a suitable organic solvent, and mix the weighed polycaprolactone into the organic solvent and dissolve it for 24 hours;
[0009] Step 4: Vacuum-assisted impregnation: The graphene oxide aerogel template is placed in the polycaprolactone precursor solution and fully immersed for 48 hours; next, the polycaprolactone precursor solution containing the graphene oxide aerogel template is transferred to a vacuum box to create and maintain a vacuum environment to ensure that the graphene oxide aerogel template is fully impregnated with the polycaprolactone precursor solution;
[0010] Step 5, preparation of graphene-based polycaprolactone composite material: taking out the graphene oxide aerogel template soaked with the polycaprolactone precursor solution and placing it in a negative pressure place formed by the operation of a high-speed fan to rapidly volatilize the organic solvent, thereby forming a directional porous graphene-based polycaprolactone composite material;
[0011] Step 6. Preparation of graphene-polycaprolactone composite materials: Place the graphene-based polycaprolactone composite material in a customized silicone mold, and put it into a drying oven for continuous heating. When the polycaprolactone in the composite material is converted into a molten state, uniformly and stepwise pressurize it in a direction perpendicular to the oriented holes until the compressive strain reaches 90%; finally, allow the hot-pressed composite material to cool naturally to obtain a highly dense graphene-polycaprolactone composite material with an ordered bionic stacking structure at the micro-nano scale.
[0012] Preferably, in step 1, the polycaprolactone is carboxyl-terminated polycaprolactone (OH-PCL-COOH), has an intrinsic viscosity IV (dl / g) of less than or equal to 0.5, and has a weight average molecular weight (Mw) of 3w.
[0013] Preferably, in step 2, the chemical cross-linking agent is ethylenediamine, which is added at a ratio of 5 vol.‰.
[0014] Preferably, in step 2, the hydrothermal temperature is 80-120°C.
[0015] Preferably, in step 2, the graphene oxide hydrogel is cut into a cuboid of 20 mm in length × 10 mm in width × 10 mm in height, and dialyzed in a 20 vol.% alcohol aqueous solution for 24 h; the dialyzed graphene oxide hydrogel is placed upright on a unidirectional freezing platform to allow ice crystals to grow along the length of the graphene oxide hydrogel; the freeze-shaped graphene oxide hydrogel is placed in a vacuum freeze dryer at a freezing temperature of -80°C to -120°C, and freeze-dried to obtain a graphene oxide aerogel template with directional porosity and lightweight characteristics; preferably, in step 2, the density of the graphene oxide aerogel template is 11 to 20 mg / cm 3 .
[0016] Preferably, in step three, the organic solvent is dichloromethane.
[0017] Preferably, in step three, the concentration of the polycaprolactone precursor solution is 100-400 mg / mL.
[0018] Preferably, in step 4, the vacuum environment is -0.85 MPa, and the vacuum environment is maintained for 10 minutes.
[0019] Preferably, in step six, the temperature of continuous heating is 100° C., and the holding time of continuous heating is 10 min.
[0020] Preferably, in step six, axial compression is adopted, and compression is performed step by step with 10% strain as an increment.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention provides a convenient and fast method for preparing bionic stacked and toughened graphene-polycaprolactone composite materials. Through pre-oriented porous aerogel templates, vacuum-assisted impregnation, step-by-step hot pressing and other processes, a multi-scale bionic stacked microstructure toughening mechanism is established, and a graphene-polycaprolactone composite material with an ordered microstructure of "brick (polycaprolactone)-mud (graphene)" imitating mother-of-pearl and high strength and high toughness is obtained. The problem of precise construction of multi-scale bionic stacked structures and controllable adjustment of mechanical toughening of low-melting point and highly brittle organic polymer materials is solved, and a new strategy is provided for realizing the toughening preparation of organic polymers, which has important application value and scientific significance.
[0023] 2. The inherent wrinkled morphology of the graphene oxide sheets in the graphene oxide aerogel template of the present invention and the large number of grafted oxygen-containing functional groups can help it to achieve a stable composite with organic polymer materials through physical and chemical cooperation, and its mechanical properties are excellent. At the same time, it has a directional and ordered three-dimensional porous network at the micro-nano scale, which can be used as an ideal reinforcing phase for strengthening and toughening organic polymer materials such as polycaprolactone. Polycaprolactone and graphene oxide templates are uniformly compounded "from bottom to top" to obtain a graphene-polycaprolactone composite material with an ordered microstructure of "brick (polycaprolactone)-mud (graphene)" imitating mother-of-pearl. The above-mentioned unique bionic stacked structure can achieve the goal of strengthening and toughening organic polymer materials by reducing interface stress, weakening interlayer shear stress, promoting interface slip, absorbing the energy generated by fracture, and inhibiting crack development. It is of great significance to realize the orderly regulation of microstructure in the confined space of organic polymer materials, the regulation of mechanical properties on demand, and functional application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a flow chart of the preparation method of the present invention.
[0025] Figure 2 The graphene oxide aerogel and microscopic porous morphology obtained by directional freezing of the present invention; wherein, Figure (a) shows the optical image of the graphene oxide aerogel cast by directional freezing; Figure (b) is obtained by observation using a scanning electron microscope. Due to the directional upward growth of ice crystals, the graphene sheets are squeezed to form a microscopic multi-level pore structure with a vertically upward orientation characteristic.
[0026] Figure 3 The graphene-polycaprolactone composite material and bionic stacked microstructure diagram of the present invention; wherein, (a) shows an optical image of the graphene-polycaprolactone composite material; (b) is a graphene-polycaprolactone composite material observed by scanning electron microscopy, which has an ordered stacked microstructure of imitating mother-of-pearl "brick (polycaprolactone)-mud (graphene)" at the micrometer scale.
[0027] Figure 4 It is a three-point bending mechanical property diagram of the graphene-polycaprolactone composite material of the present invention; wherein, (a) shows the influence of different polycaprolactone precursor solution concentrations on the three-point bending mechanical properties of the graphene-polycaprolactone composite material; b) shows the influence of different graphene oxide composite amounts on the three-point bending mechanical properties of the graphene-polycaprolactone composite material.
[0028] Figure 5 CCK-8 cytotoxicity test of the graphene-polycaprolactone composite material of the present invention;
[0029] Figure 6 This is a live-dead staining cytotoxicity experiment of the graphene-polycaprolactone composite material of the present invention;
[0030] Figure 7 It is the silicone mold used in the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] A method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material, such as Figure 1 The process diagram shown in FIG. 1 includes the following specific steps:
[0034] Step 1: For raw material preparation and processing, high-purity large-diameter graphene oxide was prepared by improved Hummer's method, and the concentration of graphene oxide precursor solution was prepared to be 2 mg / ml; polycaprolactone was purchased from Jinan Daigang Biotechnology Co., Ltd.; ethylenediamine was purchased from Chengdu Jinshan Chemical Reagent Co., Ltd.; and dichloromethane was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0035] Step 2: For the preparation of graphene oxide aerogel template, take the required volume of 2 mg / ml graphene oxide precursor solution, disperse it evenly by ultrasonication, add 5 vol.‰ of ethylenediamine, shake well, and then ultrasonicate again until it is evenly dispersed; put the above liquid into the prepared mold (an open round glass bottle with an outer diameter of 21.82 mm, an inner diameter of 19.46 mm, and a height of 57 mm), put the mold containing the liquid into a hydrothermal reactor, and perform hydrothermal reaction at 120°C for 6 hours to obtain graphene oxide hydrogel. Gel; cut the graphene oxide hydrogel into a cuboid of 20 mm (length) × 10 mm (width) × 10 mm (height), and dialyze it in a 20 vol.% alcohol aqueous solution for 24 hours; place the dialyzed graphene oxide hydrogel upright on a unidirectional freezing platform to allow ice crystals to grow along the length of the graphene oxide hydrogel; place the frozen graphene oxide hydrogel in a vacuum freeze dryer and freeze-dry it to obtain a graphene oxide aerogel template with directional porosity and light weight, such as Figure 2 shown.
[0036] Step 3: For the preparation of polycaprolactone precursor solution, weigh 6 g of polycaprolactone, measure 20 ml of dichloromethane, mix the weighed polycaprolactone into dichloromethane, and dissolve it in a sealed container for 24 hours to prepare a polycaprolactone precursor solution with a concentration of 300 mg / mL.
[0037] Step 4: For vacuum-assisted impregnation, the graphene oxide aerogel template is placed in the polycaprolactone precursor solution and fully immersed for 48 hours; next, the polycaprolactone precursor solution containing the graphene oxide aerogel template is transferred to a vacuum box, evacuated to -0.85 MPa and maintained for 10 minutes to ensure that the graphene oxide aerogel template is fully impregnated with the polycaprolactone precursor solution.
[0038] Step 5: For the preparation of graphene-based polycaprolactone composite materials, take out the graphene oxide aerogel template soaked with polycaprolactone precursor solution and place it in a negative pressure place formed by the operation of a high-speed fan to allow the dichloromethane to evaporate quickly. After the dichloromethane is completely evaporated, a directional porous graphene-based polycaprolactone composite material is formed.
[0039] Step 6: For the preparation of graphene-polycaprolactone composite material, the graphene-based polycaprolactone composite material is placed in a customized Figure 7The graphene-based polycaprolactone composite material was uniformly compressed in a direction perpendicular to the directional hole after the mold, the graphene-based polycaprolactone composite material and the copper block were naturally cooled to obtain a graphene-based polycaprolactone composite material with a size of 10 mm × 20 mm × 9 mm. The graphene-based polycaprolactone composite material was then placed in a 100°C drying oven and kept at 100°C for 10 min. After the polycaprolactone in the composite material was converted into a molten state, a copper block of the same shape and size and a thickness of 10 mm was pressed on the silicone mold. Figure 7 The 10 mm × 20 mm × 8 mm hole of the silicone mold shown in the figure is repeated, and the process of hot melting, pressurization, and cooling is repeated to obtain a graphene-based polycaprolactone composite material with a size of 10 mm × 20 mm × 8 mm; with a compression amount of 1 mm, the above operation is repeated until a graphene-polycaprolactone composite material with a size of 10 mm × 20 mm × 1 mm and having an ordered bionic stacking structure at the micro-nano scale and high density is obtained, such as Figure 3 shown.
[0040] like Figure 4 As shown, the graphene-polycaprolactone composite material has a multi-level stacked microstructure imitating mother-of-pearl, and its mechanical strength and toughness are improved by 88.85% and 72.86% respectively compared with the polycaprolactone substrate.
[0041] Example 2
[0042] A method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material, such as Figure 1 The process diagram shown in FIG. 1 includes the following specific steps:
[0043] Step 1: For raw material preparation and processing, high-purity large-diameter graphene oxide was prepared by improved Hummer's method, and the concentration of graphene oxide precursor solution was prepared to be 6 mg / ml; polycaprolactone was purchased from Jinan Daigang Biotechnology Co., Ltd.; ethylenediamine was purchased from Chengdu Jinshan Chemical Reagent Co., Ltd.; dichloromethane was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0044] Step 2: For the preparation of graphene oxide aerogel template, take the required volume of 6 mg / ml graphene oxide precursor solution, disperse it evenly by ultrasonication, add 5 vol.‰ of ethylenediamine, shake well, and then ultrasonicate again until it is evenly dispersed; put the above liquid into the prepared mold (an open round glass bottle with an outer diameter of 21.82 mm, an inner diameter of 19.46 mm, and a height of 57 mm), put the mold containing the liquid into a hydrothermal reactor, and perform hydrothermal reaction at 120°C for 6 hours to obtain graphene oxide. hydrogel; the graphene oxide hydrogel was cut into a cuboid of 20 mm (length) × 10 mm (width) × 10 mm (height), and dialyzed in a 20 vol.% alcohol aqueous solution for 24 h; the dialyzed graphene oxide hydrogel was placed upright on a unidirectional freezing platform to allow ice crystals to grow along the length of the graphene oxide hydrogel; the frozen graphene oxide hydrogel was placed in a vacuum freeze dryer and freeze-dried to obtain a graphene oxide aerogel template with directional porosity and light weight ( Figure 2 ).
[0045] Step 3: For the preparation of polycaprolactone precursor solution, weigh 6 g of polycaprolactone, measure 20 ml of dichloromethane, mix the weighed polycaprolactone into dichloromethane, and dissolve it in a sealed container for 24 hours to prepare a polycaprolactone precursor solution with a concentration of 300 mg / mL.
[0046] Step 4: For vacuum-assisted impregnation, the graphene oxide aerogel template is placed in the polycaprolactone precursor solution and fully immersed for 48 hours; next, the polycaprolactone precursor solution containing the graphene oxide aerogel template is transferred to a vacuum box, evacuated to -0.85 MPa and maintained for 10 minutes to ensure that the graphene oxide aerogel template is fully impregnated with the polycaprolactone precursor solution.
[0047] Step 5: For the preparation of graphene-based polycaprolactone composite materials, take out the graphene oxide aerogel template soaked with polycaprolactone precursor solution and place it in a negative pressure place formed by the operation of a high-speed fan to allow the dichloromethane to evaporate quickly. After the dichloromethane is completely evaporated, a directional porous graphene-based polycaprolactone composite material is formed.
[0048] Step 6: For the preparation of graphene-polycaprolactone composite material, the graphene-based polycaprolactone composite material is placed in a customized Figure 7The graphene-based polycaprolactone composite material was uniformly compressed in a direction perpendicular to the directional hole after the mold, the graphene-based polycaprolactone composite material and the copper block were naturally cooled to obtain a graphene-based polycaprolactone composite material with a size of 10 mm × 20 mm × 9 mm. The graphene-based polycaprolactone composite material was then placed in a 100°C drying oven and kept at 100°C for 10 min. After the polycaprolactone in the composite material was converted into a molten state, a copper block of the same shape and size and a thickness of 10 mm was pressed on the silicone mold. Figure 7 The 10 mm × 20 mm × 8 mm hole of the silicone mold shown in the figure is repeated, and the process of hot melting, pressurization, and cooling is repeated to obtain a graphene-based polycaprolactone composite material with a size of 10 mm × 20 mm × 8 mm; with a compression amount of 1 mm, the above operation is repeated until a graphene-polycaprolactone composite material with a size of 10 mm × 20 mm × 1 mm and having an ordered bionic stacking structure at the micro-nano scale and high density is obtained, such as Figure 3 shown.
[0049] like Figure 4 As shown in Figure 2, the graphene-polycaprolactone composite material has a multi-level stacked microstructure imitating mother-of-pearl, and its mechanical strength and toughness are improved by 222.29% and 57.26% respectively compared with the polycaprolactone substrate. Figure 5 and Figure 6 As shown, the composite material still maintains good biocompatibility and has broad application prospects in the fields of cell and tissue culture medium frames, biological scaffolds, artificial bone materials, etc.
[0050] Example 3
[0051] A method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material, such as Figure 1 The process diagram shown in FIG. 1 includes the following specific steps:
[0052] Step 1: For raw material preparation and processing, high-purity large-diameter graphene oxide was prepared by improved Hummer's method, and the concentration of graphene oxide precursor solution was prepared to be 10 mg / ml; polycaprolactone was purchased from Jinan Daigang Biotechnology Co., Ltd.; ethylenediamine was purchased from Chengdu Jinshan Chemical Reagent Co., Ltd.; and dichloromethane was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0053] Step 2: For the preparation of graphene oxide aerogel template, take the required volume of 10 mg / ml graphene oxide precursor solution, disperse it evenly by ultrasonication, add 5 vol.‰ of ethylenediamine, shake well, and then ultrasonicate again until it is evenly dispersed; put the above liquid into the prepared mold (an open round glass bottle with an outer diameter of 21.82 mm, an inner diameter of 19.46 mm, and a height of 57 mm), put the mold containing the liquid into a hydrothermal reactor, and perform hydrothermal reaction at 120°C for 6 hours to obtain graphene oxide. hydrogel; cutting the graphene oxide hydrogel into a cuboid of 20 mm (length) × 10 mm (width) × 10 mm (height), and dialyzing it in a 20 vol.% alcohol aqueous solution for 24 hours; placing the dialyzed graphene oxide hydrogel upright on a unidirectional freezing platform to allow ice crystals to grow along the length direction of the graphene oxide hydrogel; placing the frozen graphene oxide hydrogel in a vacuum freeze dryer, and freeze-drying it to obtain a graphene oxide aerogel template with directional porosity, light weight and other characteristics, such as Figure 2 shown.
[0054] Step 3: For the preparation of polycaprolactone precursor solution, weigh 6 g of polycaprolactone, measure 20 ml of dichloromethane, mix the weighed polycaprolactone into dichloromethane, and dissolve it in a sealed container for 24 hours to prepare a polycaprolactone precursor solution with a concentration of 300 mg / mL.
[0055] Step 4: For vacuum-assisted impregnation, the graphene oxide aerogel template is placed in the polycaprolactone precursor solution and fully immersed for 48 hours; next, the polycaprolactone precursor solution containing the graphene oxide aerogel template is transferred to a vacuum box, evacuated to -0.85 MPa and maintained for 10 minutes to ensure that the graphene oxide aerogel template is fully impregnated with the polycaprolactone precursor solution.
[0056] Step 5: For the preparation of graphene-based polycaprolactone composite materials, take out the graphene oxide aerogel template soaked with polycaprolactone precursor solution and place it in a negative pressure place formed by the operation of a high-speed fan to allow the dichloromethane to evaporate quickly. After the dichloromethane is completely evaporated, a directional porous graphene-based polycaprolactone composite material is formed.
[0057] Step 6: For the preparation of graphene-polycaprolactone composite material, the graphene-based polycaprolactone composite material is placed in a customized Figure 7The graphene-based polycaprolactone composite material was uniformly compressed in a direction perpendicular to the directional hole after the mold, the graphene-based polycaprolactone composite material and the copper block were naturally cooled to obtain a graphene-based polycaprolactone composite material with a size of 10 mm × 20 mm × 9 mm. The graphene-based polycaprolactone composite material was then placed in a 100°C drying oven and kept at 100°C for 10 min. After the polycaprolactone in the composite material was converted into a molten state, a copper block of the same shape and size and a thickness of 10 mm was pressed on the silicone mold. Figure 7 The 10 mm × 20 mm × 8 mm hole of the silicone mold shown in the figure is repeated, and the process of hot melting, pressurization, and cooling is repeated to obtain a graphene-based polycaprolactone composite material with a size of 10 mm × 20 mm × 8 mm; with a compression amount of 1 mm, the above operation is repeated until a graphene-polycaprolactone composite material with a size of 10 mm × 20 mm × 1 mm and having an ordered bionic stacking structure at the micro-nano scale and high density is obtained, such as Figure 3 shown.
[0058] like Figure 4 As shown, the graphene-polycaprolactone composite material has a multi-level stacked microstructure imitating mother-of-pearl, and its mechanical strength and toughness are improved by 98.85% and 28.49% respectively compared with the polycaprolactone substrate.
[0059] Example 4
[0060] like Figure 2 As shown, Figure 2 (a) Optical image showing the directional freeze-cast graphene oxide aerogel. Figure 2 (b) was observed using a scanning electron microscope. As the ice crystals grow in a directional upward direction, they squeeze the graphene sheets and form a microscopic multi-level pore structure with vertically oriented characteristics.
[0061] like Figure 3 As shown, Figure 3 (a) shows the optical image of graphene-polycaprolactone composite material; Figure 3 (b) is the graphene-polycaprolactone composite material observed by scanning electron microscopy, which has an ordered layered microstructure of "brick (polycaprolactone)-mud (graphene)" imitating mother-of-pearl at the micrometer scale. The multi-scale structural characteristics of the graphene-polycaprolactone composite material were characterized by scanning electron microscopy. It can be found that the graphene-polycaprolactone composite material has a multi-scale mother-of-pearl "brick-mud" layered structure. The unique structural characteristics can reduce interface stress, weaken interlayer shear stress, promote interface slip, absorb the energy generated by fracture, and inhibit crack development, thereby achieving the goal of strengthening and toughening organic polymer materials.
[0062] like Figure 4 As shown, Figure 4(a) shows the effect of different polycaprolactone precursor solution concentrations on the three-point bending mechanical properties of graphene-polycaprolactone composites. As the concentration of the polycaprolactone precursor solution increases, the flexural strength and bending deflection of the graphene-polycaprolactone composite first increase (100-300 mg / mL) and then decrease (400 mg / mL). The horizontal and vertical coordinates corresponding to the highest point of the curve in the figure correspond to the maximum bending deflection and maximum bending strength of the corresponding graphene-polycaprolactone composite, respectively. Therefore, it can be obtained that: the maximum bending deflection of the polycaprolactone material is 0.2244 mm, and the maximum bending strength is 3.23 MPa; the maximum bending deflection of the graphene-polycaprolactone composite prepared with 100 mg / mL precursor is 0.2878 mm, and the maximum bending strength is 6.325 MPa; the graphene-polycaprolactone composite prepared with 200 mg / mL precursor The maximum bending deflection of the graphene-polycaprolactone composite material is 0.3229mm, and the maximum bending strength is 8.49MPa; the maximum bending deflection of the graphene-polycaprolactone composite material prepared by 300mg / mL precursor is 0.3529mm, and the maximum bending strength is 10.41MPa; the maximum bending deflection of the graphene-polycaprolactone composite material prepared by 400mg / mL precursor is 0.3007mm, and the maximum bending strength is 9.627MPa.
[0063] Figure 4(b) The above is the effect of different graphene oxide compounding amounts on the three-point bending mechanical properties of graphene-polycaprolactone composite materials. The horizontal and vertical coordinates corresponding to the highest point of the curve in the figure correspond to the maximum bending deflection and maximum bending strength of the corresponding graphene-polycaprolactone composite material, so it can be obtained that: the maximum bending deflection of the polycaprolactone material is 0.2244mm, and the maximum bending strength is 3.23MPa; the maximum bending deflection of the graphene-polycaprolactone composite material (G: 5.78wt.%) prepared by the composite of graphene oxide aerogel constructed by 2mg / mL graphene oxide precursor is 0.3879mm, and the maximum bending strength is 6.1007MPa; the maximum bending deflection of the graphene-polycaprolactone composite material (G: 8.50wt.%) prepared by the composite of graphene oxide aerogel constructed by 4mg / mL graphene oxide precursor is 0.4429mm, and the maximum bending strength is 7.2964MPa; The graphene-polycaprolactone composite material (G: 10.76wt.%) prepared by compounding graphene oxide aerogel constructed by 6mg / mL graphene oxide precursor has a maximum bending deflection of 0.3529mm and a maximum bending strength of 10.41MPa; the graphene-polycaprolactone composite material (G: 13.02wt.%) prepared by compounding graphene oxide aerogel constructed by 8mg / mL graphene oxide precursor has a maximum bending deflection of 0.5232mm and a maximum bending strength of 11.5071MPa; the graphene-polycaprolactone composite material (G: 15.86wt.%) prepared by compounding graphene oxide aerogel constructed by 10mg / mL graphene oxide precursor has a maximum bending deflection of 0.2883mm and a maximum bending strength of 6.423MPa. That is, the flexural strength and bending deflection of graphene-polycaprolactone composite materials can be increased by 88% to 256% and 28% to 133% respectively compared with polycaprolactone;
[0064] Polycaprolactone has excellent biocompatibility, polymer compatibility, biodegradability and other properties. The toughened graphene-polycaprolactone composite material has better mechanical properties and can be used as a cell and tissue culture medium, biological scaffold, artificial bone material, etc.
[0065] Application effect of materials:
[0066] like Figure 5As shown, according to the CCK-8 cytotoxicity test, after the L-929 cells were treated with the extract medium for 24 hours, the cell viability of the graphene-polycaprolactone composite material group and the polycaprolactone group was 86.3% ± 92.6% and 84.3% ± 93.6%, respectively. After the cells were treated with the extract for 48 hours and 72 hours, respectively, there was no significant change in the viability of the two groups of cells, especially after 72 hours of culture, the viability of the three groups of cells was still more than 90%, 81.5% ± 103.2% and 83.6% ± 107%, respectively. In addition, the statistical results of 24 hours, 48 hours, and 72 hours showed that there was no statistical difference in cell viability between the graphene-polycaprolactone composite material group and the polycaprolactone group (P>0.05). This shows that under the experimental conditions, the two groups of samples had no obvious toxic effects on the survival rate and cell viability of L-929 cells, and the cells grew well.
[0067] like Figure 6 As shown, according to the live-dead staining cytotoxicity test, when L-929 cells were treated with the extract medium for 24, 48 and 72 hours, a large number of live cells (green fluorescence represents live cells) and a small number of dead cells (red fluorescence represents dead cells) were visible in the field of view of the graphene-polycaprolactone composite material group and the polycaprolactone group, and the number of live and dead cells increased significantly over time. This shows that the cytotoxicity of each group is basically the same, and the results are consistent with the CCK8 results. In summary, the above results show that the doping of the three-dimensional graphene oxide network has little effect on cell survival rate, and the composite material still maintains good biocompatibility, and has broad application prospects in the fields of cell and tissue culture medium frames, biological scaffolds, artificial bone materials, etc.
[0068] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material, characterized in that: The steps include: Step 1: Raw material preparation and processing: high-purity large-diameter graphene oxide was prepared by using the improved Hummer's method, and the concentration of the graphene oxide precursor solution was 2-10 mg / ml; polycaprolactone was purchased from Jinan Daigang Biotechnology Co., Ltd.; Step 2: Preparation of graphene oxide aerogel template: Graphene oxide precursor solution is assisted by chemical crosslinking agent to obtain graphene oxide hydrogel by hydrothermal assembly, and then a graphene oxide aerogel template with directional porosity and light weight is obtained by steps of water-alcohol dialysis, directional freezing, vacuum freeze drying, etc.; Step 3, preparation of polycaprolactone precursor solution: determine the concentration and volume of the polycaprolactone precursor solution, quantitatively weigh polycaprolactone, select a suitable organic solvent, and mix the weighed polycaprolactone into the organic solvent and dissolve it for 24 hours; Step 4: Vacuum-assisted impregnation: The graphene oxide aerogel template is placed in the polycaprolactone precursor solution and fully immersed for 48 hours; next, the polycaprolactone precursor solution containing the graphene oxide aerogel template is transferred to a vacuum box to create and maintain a vacuum environment to ensure that the graphene oxide aerogel template is fully impregnated with the polycaprolactone precursor solution; Step 5, preparation of graphene-based polycaprolactone composite material: taking out the graphene oxide aerogel template soaked with the polycaprolactone precursor solution and placing it in a negative pressure place formed by the operation of a high-speed fan to rapidly volatilize the organic solvent, thereby forming a directional porous graphene-based polycaprolactone composite material; Step 6. Preparation of graphene-polycaprolactone composite materials: Place the graphene-based polycaprolactone composite material in a customized silicone mold, and put it into a drying oven for continuous heating. When the polycaprolactone in the composite material is converted into a molten state, uniformly and stepwise pressurize it in a direction perpendicular to the oriented holes until the compressive strain reaches 90%; finally, allow the hot-pressed composite material to cool naturally to obtain a highly dense graphene-polycaprolactone composite material with an ordered bionic stacking structure at the micro-nano scale.
2. The method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material according to claim 1, characterized in that: In step 1, the polycaprolactone is carboxyl-terminated polycaprolactone OH-PCL-COOH, has an intrinsic viscosity IVdl / g less than or equal to 0.5, and a weight average molecular weight Mw of 3w.
3. The method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material according to claim 1, characterized in that: In step 2, the chemical cross-linking agent is ethylenediamine, which is added at a ratio of 5 vol.‰.
4. The method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material according to claim 1, characterized in that: In step 2, the hydrothermal temperature is 80-120°C.
5. The method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material according to claim 1, characterized in that: In step 2, the graphene oxide hydrogel is cut into a cuboid of 20 mm in length, 10 mm in width and 10 mm in height, and dialyzed in a 20 vol.% alcohol aqueous solution for 24 hours; the dialyzed graphene oxide hydrogel is placed upright on a unidirectional freezing platform to allow ice crystals to grow along the length of the graphene oxide hydrogel; the frozen graphene oxide hydrogel is placed in a vacuum freeze dryer at a freezing temperature of -80°C to -120°C, and freeze-dried to obtain a graphene oxide aerogel template with directional porosity and lightweight characteristics; preferably, in step 2, the density of the graphene oxide aerogel template is 11 to 20 mg / cm 3 .
6. The method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material according to claim 1, characterized in that: In step three, the organic solvent is dichloromethane.
7. The method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material according to claim 1, characterized in that: In step three, the concentration of the polycaprolactone precursor solution is 100-400 mg / mL.
8. The method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material according to claim 1, characterized in that: In step 4, the vacuum environment is -0.85 MPa, and the vacuum environment is maintained for 10 minutes.
9. The method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material according to claim 1, characterized in that: In step six, the continuous heating temperature is 100° C., and the continuous heating holding time is 10 minutes.
10. The method for preparing a biomimetic laminated toughened graphene-polycaprolactone composite material according to claim 1, characterized in that: In step six, axial compression is used, with stepwise compression at 10% strain increments.
